2020
DOI: 10.1029/2020gl087295
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of QBO‐MJO Connection in CMIP6 Models

Abstract: Observational analysis has indicated a strong connection between the stratospheric quasi‐biennial oscillation (QBO) and tropospheric Madden‐Julian oscillation (MJO), with MJO activity being stronger during the easterly phase than the westerly phase of the QBO. We assess the representation of this QBO‐MJO connection in 30 models participating in the Coupled Model Intercomparison Project 6. While some models reasonably simulate the QBO during boreal winter, none of them capture a difference in MJO activity betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 24 publications
1
44
1
Order By: Relevance
“…The biased QBO‐MJO relationship in MetUM‐GOML1 is considered to be associated with weak QBO‐induced temperature anomalies in the tropical tropopause or to errors in MJO vertical structure (J. C. K. Lee & Klingaman, 2018). By comparing the 30 CMIP6 models, it is shown that none of the models are able to capture the observed QBO‐MJO connection (H. Kim, Caron, et al, 2020).…”
Section: Recent Progress In Understanding Modeling and Predicting Tmentioning
confidence: 99%
“…The biased QBO‐MJO relationship in MetUM‐GOML1 is considered to be associated with weak QBO‐induced temperature anomalies in the tropical tropopause or to errors in MJO vertical structure (J. C. K. Lee & Klingaman, 2018). By comparing the 30 CMIP6 models, it is shown that none of the models are able to capture the observed QBO‐MJO connection (H. Kim, Caron, et al, 2020).…”
Section: Recent Progress In Understanding Modeling and Predicting Tmentioning
confidence: 99%
“…This relationship provides an additional pathway for sources of predictability on seasonal to subseasonal time scales (Lim et al, 2019;Liu et al, 2014;Marshall et al, 2017). However, it is a major challenge to exploit this source because current general circulation models (GCM) often struggle to simulate both the MJO and QBO (Jiang et al, 2015;H. Kim et al, 2020;Scaife et al, 2014) and the physical mechanism behind their relationship is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship provides an additional pathway for sources of predictability on seasonal to subseasonal time scales (Lim et al., 2019; Liu et al., 2014; Marshall et al., 2017). However, it is a major challenge to exploit this source because current general circulation models (GCM) often struggle to simulate both the MJO and QBO (Jiang et al., 2015; H. Kim et al., 2020; Scaife et al., 2014) and the physical mechanism behind their relationship is not well understood. Previous studies show that the QBO‐MJO relationship is peculiar for the following reasons: (i) it is only observed during boreal winter (Densmore et al., 2019; Hendon & Abhik, 2018; Nishimoto & Yoden, 2017; Son et al., 2017; Yoo & Son, 2016), (ii) an analogous relationship between the QBO and other modes of tropical variability, such as convectively coupled equatorial waves (CCEWs), is less clear (Abhik et al., 2019), and (iii) the relationship only appears after around 1980 (Klotzbach et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, climate models struggle to capture the prominent features of either the MJO or QBO, or both (e.g., Ahn et al, 2017; Butchart et al, 2018). For instance, both Coupled Model Intercomparison Project Phase 5 (CMIP5) and Phase 6 (CMIP6) models fail to reproduce the QBO‐MJO connection (Kim et al, 2020; Lim & Son, 2020). Unlike climate models, S2S prediction models show a hint of the QBO‐MJO connection.…”
Section: Introductionmentioning
confidence: 99%